2016
DOI: 10.1186/s12866-016-0896-z
|View full text |Cite
|
Sign up to set email alerts
|

Small proteins in cyanobacteria provide a paradigm for the functional analysis of the bacterial micro-proteome

Abstract: BackgroundDespite their versatile functions in multimeric protein complexes, in the modification of enzymatic activities, intercellular communication or regulatory processes, proteins shorter than 80 amino acids (μ-proteins) are a systematically underestimated class of gene products in bacteria. Photosynthetic cyanobacteria provide a paradigm for small protein functions due to extensive work on the photosynthetic apparatus that led to the functional characterization of 19 small proteins of less than 50 amino a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 56 publications
(86 citation statements)
references
References 73 publications
(82 reference statements)
3
83
0
Order By: Relevance
“…However, several studies revealed the involvement of small proteins in essential regulatory and other processes (Storz et al, 2014 ). The detection and functional characterization of small proteins in cyanobacteria has received particular attention (Baumgartner et al, 2016 ). We therefore decided to add their genes, if they were conserved and had a minimum length of 50 amino acids, to the other two genomes, leading to the numbers presented in Figure 4 .…”
Section: Resultsmentioning
confidence: 99%
“…However, several studies revealed the involvement of small proteins in essential regulatory and other processes (Storz et al, 2014 ). The detection and functional characterization of small proteins in cyanobacteria has received particular attention (Baumgartner et al, 2016 ). We therefore decided to add their genes, if they were conserved and had a minimum length of 50 amino acids, to the other two genomes, leading to the numbers presented in Figure 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Knowledge about the functions of small proteins in bacteria is limited, but small proteins have recently achieved attention (reviewed in [ 15 , 18 ]). For instance, Baumgartner et al [ 67 ] confirmed five small proteins in Synechocystis by Western blot. Neuhaus et al [ 11 ] detected 72 novel small genes in the intergenic regions of the E .…”
Section: Discussionmentioning
confidence: 99%
“…Samples for protein and amino acid extraction were taken prior to and in short intervals after adding NH 4 Cl in a final concentration of 10 mM. Proteins were extracted from cells harvested by centrifugation, separated by SDS-PAGE and transferred to nitrocellulose membranes as described previously ( 52 ). Membranes were blocked with TBS-T containing 5% milk powder and probed with sera containing anti-IF17 (1:2000) or anti-TrxA (1:5000).…”
Section: Methodsmentioning
confidence: 99%